ТЕРМИНЫ «ЭКОЛОГИЯ» И «ЭКОЛОГИЧЕСКИЙ» В ОТЕЧЕСТВЕННОМ ПОЧВОВЕДЕНИИ† - Migunova, E. S. (Forestry and Forest Melioration, 2018)
The ecology which is engaged in studying of the relationships of vegetation with an environment was formed at the turn of the XIX-XX centuries. The soil is "home", "dwelling place" of plants. Recently the soils are studied as the special natural bodies, regardless of vegetation. Only N. M. Sibirtsev understood that the direction created in the centuries-old process of learning soils as a plants habitat is a "completely legal". He grounded appropriateness of the unification of theories about soil as a natural body established by Dokuchaev and about plants habitat, existing for many centuries. The scientist claimed that these two sections only together made a single naturally scientific soil science. According to the national postulate "what is the soil of the earth, so it is the forest", A. A. Krudener developed a conjugate classification of forests and soils, in which the forests are placed on the build-up of soil fertility. In this case it is revealed that the composition and productivity of plantations are determined by the mechanical composition of soils and parent rock material, but not by the genetic types of soils as Morozov supposed. The composition of the forests is defined first of all by the content of two bio-elements in the soils - phosphorus and potassium. At the assessment of soils as a habitat the crucial factor is the mineral composition of the soils, caused by the source rock, but not by the structure of their profile, their genetic types. Following N. M. Sibirtsev, it should be expressed the belief about the necessity of allocation in the soil science of two large equal sections - genetic soil science which studies soils as a natural body and ecological soil science learning soils as a habitat. Fertility is the main quality which distinguishes soils from all other natural bodies, their incomparable function, mission on Earth because without plants, performing photosynthesis, the process that transforms inorganic compounds into organic, life is impossible. Forest typology systematics is based on the accounting only limited ecological resources on Earth - the heat, moisture and food. It is believed that with the lapse of time, these principles will be used for classification of all living population of planet.